Temperamental and socioeconomic factors associated with traumatic dental injuries among children aged 0–17 years in the Swedish BITA study. Issue 5 (11th May 2015) - Oldin, Anna; Lundgren, Jesper; Norén, Jörgen G.; Robertson, Agneta
Abstract Aim The aim of the study was to identify individual risk factors for traumatic dental injuries (TDI) among Swedish children aged 0–17 years. The studied risk factors were temperamental reactivity of the child, family structure, parent's country of birth, and the socioeconomic status of the family represented by parental education and occupation. Subjects and methods The study included 2363 children in four different age cohorts at 12 public dental service clinics in Sweden, representing different types of demographic areas, both rural and urban. Data were collected from parents and children through an interview and questionnaires. Results The more social and active children in the two older age cohorts showed less occasions of TDI. Having one parent/guardian protected the child from dental injury just as well as two parents/guardians. Parents born outside of the Nordic countries showed children with less TDI. Low parental education was related to more occasions of TDI among the children. Conclusions This study has increased the knowledge on certain individual risk factors for TDI. To prevent dental injuries, information could be given to families and children at risk.